International evidence on the economics of happiness and its impact on nation growth and fertility - V. Rasiah, R. Ratneswary (2015)
Recent literature on developed countries have shown evidence that, despite enjoying rapid growth and higher levels of material well-being, the people in these countries do not necessarily enjoy higher levels of happiness. In fact, there appears to be a declining trend in the levels of happiness among the majority, and this is believed to be related to an increase in stress-related illnesses that could bring about a decline in productivity, reductions in fertility rates; a decline in social trust, a rise in suicide rates, an unprecedented increase in crime rates and a rapid degradation of the environment. Further investigations must be carried out to determine what enables or hinders happiness, so that nations can make informed policy decisions that are necessary to ensure sustainable economic development takes place, while improving mankind’s happiness. This study examined the economic determinants of happiness and its impact on economic growth and fertility, based on the Set-Point, Cognitive and Affective theories of happiness. The study employed two methodologies to achieve its objectives. For the first objective, the study employed the pooled mean group estimator (PMG) to estimate the dynamic heterogeneous panel model involving ten countries with data spanning from 1973 to 2012, while the generalised-method-of-moments (GMM) estimators was utilised for the second and third objectives of this study involving fifty countries for the period 2000 to 2012. The results reveal that happiness had a positive long run relationship with income, unemployment, carbon emission, and education; a negative long run relationship with inflation and income inequality, while institutional quality was not significant in explaining happiness. For the second objective on the impact of happiness on economic growth, it was found that happiness had a significant and positive impact on economic growth, while the results of the third objective on the impact of happiness on fertility showed that while happiness had a significantly positive impact on fertility, happiness-squared was found to significantly cause fertility to decline, revealing the existence of an “inverted U” relationship. This study recommends the use of happiness-centred approaches to policy making in aiding policy makers in planning and implementing policies, by taking into account the subjective well-being of its people, aside from focusing on the extrinsic aspect of the economy, when considering economic growth